Detection of polled intersex syndrome (PIS) and its effect on phenotypic traits in goats. Issue 6 (11th November 2020) - Zhang, Shaoli; Cao, Xinyuan; Li, Yu; Wang, Ke; Yuan, Ming; Lan, Xianyong
Abstract: Polled intersex syndrome (PIS), a physiological defect associates polledness and intersexuality, will directly affect the reproduction and other phenotypic traits of goats, thus, it is a hazard to the development of the goat industry. Recent studies have revealed that goat PIS was caused by an 11.7-kb deletion located in chromosome 1q43, but its DNA detection method was little reported. Herein, a total of 503 goats from three goat breeds were used to successfully establish a simple, rapid, accurate and effective method for the detection of goat PIS mutation. Furthermore, based on this assay, the associations between the PIS mutation and growth traits were analyzed in Guanzhong dairy goats. These findings would provide the potential practical application for molecular breeding to accelerate the development of the goat industry.